The Intra-EU Relocation Scheme of 2015: A Test Run for a Dublin Reform - Carolin Nieswandt (International Migration, 2025)
In 2015, the first obligatory scheme re-distributing forced migrants from Italy and Greece to other EU member states was launched. The scheme anticipated the intra-EU relocation of 160,000 people in 20.167emyears. Ultimately, as few as 34,705 have actually been resettled. Drawing on Bourdieu's field-theoretical approach, this paper treats the relocation scheme as an attempt to appease conflicts over responsibility-sharing by integrating a relocation procedure into the Dublin system. In so doing, the scheme paved the way for the new solidarity mechanism which will enter into force in 2026 and targets at 30,000 relocations each year. Based on a qualitative investigation, the paper analyses the administrative design of the relocation scheme, and how this implied a redefinition of responsibilities within the European field of asylum administration. Second, the paper works out how this triggered struggles around the scheme's implementation and works out actors' relative capacity of enforcement and refusal.
Keywords: 300; bureaucratic field; common European asylum system; intra-EU relocation; responsibility-sharing; transnational cooperation